2015
DOI: 10.1063/1.4907733
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio dynamics of the cytochrome P450 hydroxylation reaction

Abstract: The iron(IV)-oxo porphyrin π-cation radical known as Compound I is the primary oxidant within the cytochromes P450, allowing these enzymes to affect the substrate hydroxylation. In the course of this reaction, a hydrogen atom is abstracted from the substrate to generate hydroxyiron(IV) porphyrin and a substrate-centered radical. The hydroxy radical then rebounds from the iron to the substrate, yielding the hydroxylated product. While Compound I has succumbed to theoretical and spectroscopic characterization, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
3
7
0
Order By: Relevance
“…This observation of extremely fast rebound trajectories and slightly slower rebound trajectories is in good agreement with Goldberg’s kinetic measurements of a corrole-ligated Fe­(OH) complex where both concerted and stepwise rebound pathways were observed . These life-time measurements are also in the range of previous ab initio dynamic simulations of cytochrome P450 enzyme models , and Houk’s dynamics simulations of radical oxygen rebound during the oxidation of isobutane by dimethyldioxirane . Moreover, similar to the ideas proposed by Goldberg and co-workers, Newcomb et al, and Sarkar et al, our trajectory results support the viewpoint that rebound is perhaps better considered a dynamically concerted process rather than a full stepwise process.…”
Section: Resultssupporting
confidence: 89%
“…This observation of extremely fast rebound trajectories and slightly slower rebound trajectories is in good agreement with Goldberg’s kinetic measurements of a corrole-ligated Fe­(OH) complex where both concerted and stepwise rebound pathways were observed . These life-time measurements are also in the range of previous ab initio dynamic simulations of cytochrome P450 enzyme models , and Houk’s dynamics simulations of radical oxygen rebound during the oxidation of isobutane by dimethyldioxirane . Moreover, similar to the ideas proposed by Goldberg and co-workers, Newcomb et al, and Sarkar et al, our trajectory results support the viewpoint that rebound is perhaps better considered a dynamically concerted process rather than a full stepwise process.…”
Section: Resultssupporting
confidence: 89%
“…After IM1 HA , a second electron is transferred to form P Hy , resulting in a close-shell porphyrin group (doubly occupied a 2u orbital) and an iron­(III) state with occupation π* xz 2 π* yz 1 in the doublet spin state and π* xz 1 π* yz 1 σ* z 2 1 in the quartet spin state. Overall, the optimized geometries match previous calculations of substrate hydroxylation reactions by P450 CpdI models well and find analogous distances, charge distributions, and structures. …”
Section: Resultssupporting
confidence: 74%
“…The imaginary frequencies, therefore, are not dramatically different between the model A II and model A III structures and would implicate similar kinetic isotope effects for replacing hydrogen by deuterium due to a similar shape of the potential energy profile around the transition state. These values are typical for hydrogen atom abstraction transition state and seen before for P450 model reactions. The large imaginary frequency in the hydrogen atom abstraction transition states will result in a large kinetic isotope effect and a significant amount of quantum chemical tunneling for the reaction. , After the radical intermediate, a small rebound barrier via TS2 leads to the hydroxylated methoxy group products 4,2 P Hy,A with large exothermicity. From the hydroxylated methoxy group, a subsequent proton relay from the alcohol group to the methoxy oxygen atom leads to deformylation.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…1). Ab initio molecular dynamics simulations have found that D is converted to E in ∼ 0.1 ps (21). Thus, protective HT to the protein surface should not approach this timescale, lest it defeat normal enzyme function, but could be useful to prevent ROS formation from compound I in the absence of substrate (the R-H substrate shown in Fig.…”
Section: Resultsmentioning
confidence: 99%